Humoral immune response to heat shock protein 60 of Aggregatibacter actinomycetemcomitans and cross-reactivity with malondialdehyde acetaldehyde-modified LDL - Kyrklund, Mikael (PLoS One, 2020)
Atherosclerosis is a chronic inflammatory disease and major cause of mortality worldwide. One of the crucial steps for atherosclerotic plaque development is oxidation of low-density lipoprotein (LDL). Through the oxidation, highly immunogenic epitopes are created and the immune system is activated. Association between atherosclerosis and periodontal diseases is well documented, and one of the main oral pathogens common in periodontitis is Aggregatibacter actinomycetemcomitans (Aa). Heat shock protein 60 (HSP60) is an important virulence factor for Aa bacteria and a strong activator of the immune system. Cross-reactivity of HSP60 and oxidized LDL (OxLDL) antibodies could be a potential mechanism in the progression of atherosclerosis and one possible link between atherosclerosis and periodontitis. Human plasma samples from neonates and mothers were analyzed to determine if antibody titer to Aa-HSP60 protein is already present in newborns. Further objectives were to characterize antibody response in Aa-HSP60 immunized mice and to determine possible antibody cross-reaction with oxidized LDL. We demonstrated that newborns already have IgM antibody levels to Aa-HSP60. We also showed that in mice, Aa-HSP60 immunization provoked IgG and IgM antibody response not only to Aa-HSP60 but also to malondialdehyde acetaldehyde-modified LDL (MAA-LDL). Competition assay revealed that the antibodies were specific to Aa-HSP60 and cross-reacted with MAA-LDL. Our results suggest a possibility of molecular mimicry between Aa-HSP60 and MAA-LDL, making it intriguing to speculate on the role of HSP60 protein in atherosclerosis that manifests at young age.